Unveiling Shared Thematic Threads: A Comparative Study of Jamil Buthainah and Sir Philip Sidney - Abdulqawi A. S. Altobbai (Taez University, 2024)
This paper undertakes a comparative study of two poets from different cultures and eras: Jamil Buthainah, a late seventh-century Arab Udhri poet, and Sir Philip Sidney, an English Elizabethan poet. Based on Jamil Buthainah's Diwan and Sidney's sonnets in Astrophil and Stella, the analysis focuses on four shared thematic threads: the blamers and slanderers, the portrayal of the beloved, the beloved's eyes, and the speakers' idealization of their love objects. Rather than seeking to identify any influence of one poet on the other, as there was none, this study highlights the poets' similar experiences in love-both were deeply in love but did not marry their beloveds. Additionally, both works exclusively address the theme of the speakers' thwarted love for their women. This paper aims to explore the similarities and differences in how Jamil Buthainah and Sidney loved and expressed their love, examining where their experiences converge and diverge. The goal is to gain a deeper understanding of the diversity and richness of poetic expression across different ages and cultures.